# How do you differentiate #g(x) = (5x-2)(x^2+1)# using the product rule?

# g'(x) = 2x(5x - 2 ) + 5(x^2 + 1 )#

applying the product rule to differentiate

If f(x).h(x) = g(x)

g'(x) would then equal f(x).h'(x) plus h(x).f'(x)................(A)

putting these values in place of (A)

By signing up, you agree to our Terms of Service and Privacy Policy

To differentiate ( g(x) = (5x-2)(x^2+1) ) using the product rule, you apply the formula ( (uv)' = u'v + uv' ). Let ( u = 5x - 2 ) and ( v = x^2 + 1 ). Then:

( u' = 5 ) (derivative of ( 5x - 2 ) with respect to ( x ))

( v' = 2x ) (derivative of ( x^2 + 1 ) with respect to ( x ))

Now, applying the product rule:

( g'(x) = (5)(x^2 + 1) + (5x - 2)(2x) )

( g'(x) = 5x^2 + 5 + 10x^2 - 4x )

( g'(x) = 15x^2 - 4x + 5 )

So, the derivative of ( g(x) ) with respect to ( x ) is ( 15x^2 - 4x + 5 ).

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- How do you find the derivative (quotient rule) for #(x^2 + 8x + 3)/sqrtx#?
- How do you differentiate #g(x) =x^2cotx# using the product rule?
- How do you differentiate #f(x)=1/x*e^(x^2)# using the product rule?
- How do you differentiate # y =sin(ln(cos x)) # using the chain rule?
- How do you differentiate #2xy=y^2-x^2/y#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7